The Montreal Cognitive Assessment: Normative Data from a Large Swedish Population-Based Cohort. - Borland, Emma; Nägga, Katarina; Nilsson, Peter M; Minthon, Lennart; Nilsson, Erik D; Palmqvist, Sebastian (J Alzheimers Dis, 2017)
BACKGROUND: The Montreal Cognitive Assessment (MoCA) has a high sensitivity for detecting cognitive dysfunction. Swedish normative data does not exist and international norms are often derived from populations where cognitive impairment has not been screened for and not been thoroughly assessed to exclude subjects with dementia or mild cognitive impairment. OBJECTIVE: To establish norms for MoCA and develop a regression-based norm calculator based on a large, well-examined cohort. METHODS: MoCA was administered on 860 randomly selected elderly people from a population-based cohort from the EPIC study. Cognitive dysfunction was screened for and further assessed at a memory clinic. After excluding cognitively impaired participants, normative data was derived from 758 people, aged 65-85. RESULTS: MoCA cut-offs (-1 to -2 standard deviations) for cognitive impairment ranged from <25 to <21 for the lowest educated and <26 to <24 for the highest educated, depending on age group. Significant predictors for MoCA score were age, sex and level of education. CONCLUSION: We present detailed normative MoCA data and cut-offs according to the DSM-5 criteria for cognitive impairment based on a large population-based cohort of elderly individuals, screened and thoroughly investigated to rule out cognitive impairment. Level of education, sex, and age should be taken in account when evaluating MoCA score, which is facilitated by our online regression-based calculator that provide percentile and z-score for a subject's MoCA score.

Copeptin, a Marker of Vasopressin, Predicts Vascular Dementia but not Alzheimer's Disease. - Nilsson, Erik D; Melander, Olle; Elmståhl, Sölve; Lethagen, Eva; Minthon, Lennart; Pihlsgård, Mats; Nägga, Katarina (J Alzheimers Dis, 2016)
BACKGROUND: Copeptin is a reliable surrogate marker for the neurohypophyseal hormone vasopressin. Elevated plasma level of copeptin has been associated with cardiovascular and metabolic disease risk. OBJECTIVE: To investigate the association between copeptin and risk of dementia. METHODS: In all, 18,240 individuals from Malmö, Sweden, were examined between 2002 and 2006 (mean age 69.3 years, 69.8% men). Incident cases of dementia until 31 December 2009 were identified by linkage with the Swedish National Patient Register. To validate the dementia diagnoses, medical records as well as laboratory and neuroimaging data were carefully reviewed. Baseline level of copeptin was measured in frozen plasma in: (1) all participants who were diagnosed with dementia during follow-up, (2) a random sample of 5100 individuals of the cohort. RESULTS: During a median follow-up of 4.2 years, there were 374 incident dementia cases (age range 60-83 years at baseline): 120 were classified as Alzheimer's disease (AD), 84 as vascular dementia (VaD), and 102 as mixed dementia. In logistic regressions adjusted for cardiovascular risk factors, baseline level of copeptin predicted incident VaD (Odds ratio (OR) 1.30 per 1 SD increase in log copeptin, 95% CI 1.03-1.64). Copeptin did not predict incidence of all-cause dementia (OR 1.05, 95% CI 0.94-1.18), AD (OR 0.97, 95% CI 0.79-1.18), or mixed dementia (OR 0.85, 95% CI 0.68-1.05). CONCLUSION: Elevated plasma level of copeptin is a risk marker for incident VaD, but not for incident AD. This suggests that the vasopressin hormonal system might be involved in the development of VaD.

A Genetic Variant of the Sortilin 1 Gene is Associated with Reduced Risk of Alzheimer's Disease. - Andersson, Carl-Henrik; Hansson, Oskar; Minthon, Lennart; Andreasen, Niels; Blennow, Kaj; Zetterberg, Henrik; Skoog, Ingmar; Wallin, Anders; Nilsson, Staffan; Kettunen, Petronella (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a neurodegenerative disorder represented by the accumulation of intracellular tau protein and extracellular deposits of amyloid-β (Aβ) in the brain. The gene sortilin 1 (SORT1) has previously been associated with cardiovascular disease in gene association studies. It has also been proposed to be involved in AD pathogenesis through facilitating Aβ clearance by binding apoE/Aβ complexes prior to cellular uptake. However, the neuropathological role of SORT1 in AD is not fully understood. To evaluate the associations between gene variants of SORT1 and risk of AD, we performed genetic analyses in a Swedish case-control cohort. Ten single nucleotide polymorphisms (SNPs), covering the whole SORT1 gene, were selected and genotyped in 620 AD patients and 1107 controls. The SNP rs17646665, located in a non-coding region of the SORT1 gene, remained significantly associated with decreased risk of AD after multiple testing (pc = 0.0061). In addition, other SNPs were found to be nominally associated with risk of AD, as well as altered cognitive function and the CSF biomarker Aβ42, but these associations did not survive correction for multiple testing. The fact that SORT1 has been strongly associated with risk of cardiovascular disease is intriguing as cardiovascular disease is also regarded as a risk factor for AD. Finally, increased knowledge about SORT1 function has a potential to increase our understanding of APOE, the strongest risk factor for AD.

Cerebrospinal fluid levels of β-amyloid 1-42, but not of tau, are fully changed already 5 to 10 years before the onset of Alzheimer dementia. - Buchhave, Peder; Minthon, Lennart; Zetterberg, Henrik; Wallin, Asa K; Blennow, Kaj; Hansson, Oskar (Arch Gen Psychiatry, 2012)
CONTEXT: Early detection of prodromal Alzheimer disease (AD) is important because new disease-modifying therapies are most likely to be effective when initiated during the early stages of disease. OBJECTIVES: To assess the ability of the cerebrospinal fluid (CSF) biomarkers total tau (T-tau), phosphorylated tau (P-tau), and β-amyloid 1-42 (Aβ42) to predict future development of AD dementia within 9.2 years in patients with mild cognitive impairment (MCI) and to compare CSF biomarkers between early and late converters to AD. DESIGN: A clinical study with a median follow-up of 9.2 years (range, 4.1-11.8 years). SETTING: Memory disorder clinic. Patients A total of 137 patients with MCI who underwent lumbar puncture at baseline. MAIN OUTCOME MEASURE Conversion to AD dementia. RESULTS: During follow-up, 72 patients (53.7%) developed AD and 21 (15.7%) progressed to other forms of dementia. At baseline, CSF Aβ42 levels were reduced and T-tau and P-tau levels were elevated in patients who converted to AD during follow-up compared with nonconverters (P < .001). Baseline CSF Aβ42 levels were equally reduced in patients with MCI who converted to AD within 0 to 5 years (early converters) compared with those who converted between 5 and 10 years (late converters). However, CSF T-tau and P-tau levels were significantly higher in early converters vs late converters. A baseline Aβ42:P-tau ratio predicted the development of AD within 9.2 years with a sensitivity of 88%, specificity of 90%, positive predictive value of 91%, and negative predictive value of 86%. CONCLUSIONS: Approximately 90% of patients with MCI and pathologic CSF biomarker levels at baseline develop AD within 9 to 10 years. Levels of Aβ42 are already fully decreased at least 5 to 10 years before conversion to AD dementia, whereas T-tau and P-tau seem to be later markers. These results provide direct support in humans for the hypothesis that altered Aβ metabolism precedes tau-related pathology and neuronal degeneration.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Follow-Up Studies; Humans; Male; Mild Cognitive Impairment; Peptide Fragments; Predictive Value of Tests; tau Proteins; Time Factors